Peran Bank BUMN dalam Program Green Finance - Basrawi Mukhry; Muammar khadafi (Yayasan Tri Edukasi Ilmiah, 2024)
Green Financing is a broad term that can refer to financial investments that flow into sustainable development projects and initiatives, environmental products and policies that encourage sustainable economic development. This research aims to analyze the role of banking in green finance in Indonesia. The focus of Green activities Financing itself is providing financing for projects or development that takes into account the balance between the economy, social and environment. To unite the steps of commercial banks in Indonesia in green financing, the government issued regulations regarding the Implementation of Sustainable Finance for Financial Services Institutions, Issuers and Public Companies.